The effectiveness of non-dominant hand in performing oral hygiene care - Normaliza Ab Malik; Aws Hashim Ali Al-Khadim; Muhammad Syafiq Alauddin; Siti Nur Farhanah Mohd Desa; Azlan Jaafar (UPM Press, 2024)
Indexed by Scopus